Pengaruh Peran Kepemimpinan Terhadap Kinerja Karyawan Melalui Motivasi Kerja Pada PT. Central Motor Wheel Indonesia Karawang Division - Maharani Aulia Anggraeni; Enjang Suherman; Laras Ratu Khalida (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
One of the many variables that may affect employee performance is the role of leadership, but there is a discrepancy in the effect of leadership roles on employee performance. Therefore, a mediating variable is needed that links leadership roles and employee performance, namely work motivation. To form a strong and productive team, a leadership role is needed. Thus, the purpose of this study is to determine the significance of the relationship between leadership roles on performance through work motivation at PT Central Motor Wheel Indonesia Karawang Division. This research uses quantitative methodology with descriptive and verification analysis. The analysis method used is SEM Smart Pls. There are 419 workers at PT. central Motor Wheel Karawang Division. The sample of this study was selected by collecting 81 respondents who fit the criteria. The process of collecting research data by distributing questionnaires. The results of the study state that the role of leadership significantly affects work motivation, the role of leadership has no significant effect on performance, work motivation has a significant effect on increasing performance, employee performance is strongly influenced by the role of leadership through motivation as mediation.